Organizational Commitment, Psychological Contract Fulfillment and Job Performance: A Longitudinal Quanti-qualitative Study - Maia,Leticia Gomes (2015)
The goals of this study are to contribute to the understanding of the development of organizational commitment and to explore the relations among psychological contract fulfillment, organizational commitment, and job performance. This paper reports the findings of a longitudinal quanti-qualitative study conducted with newcomers over three years. We identified four trajectories of commitment development: Learning to Love, High Match, Honeymoon Hangover and Learning to Hate. The last one is originally proposed in this study, and it is represented by individuals who began work highly committed to the organization, but then their commitment levels decreased dramatically over time. We discuss some characteristics associated with these trajectories. Our results corroborate the assumption that psychological contract fulfillment is positively related to commitment. Nevertheless, our findings about the relationship between commitment and job performance were different according to the trajectories. The trajectories Learning to Love and Learning to Hate support the assumption that higher commitment levels would lead to better performance, and vice versa; however, the trajectories High Match and Honeymoon Hangover contradict it. We offer and discuss some possible explanations for these findings.